PERTUMBUHAN DAN PERKEMBANGAN STRUKTUR ANATOMI, BENTUK, TIPE, DAN UKURAN AMILUM UMBI SUWEG (Amorphophallus paeoniifolius) - Rosyadah, Salma; Ratnawati, Ratnawati (Kingdom: The Journal of Biological Studies, 2024)
Abstract. The purpose of this research is to investigate growth and development of the anatomical structure of elephant foot yam tubers (Amorphophallus paeoniifolius), the shape, type and size of starch in elephant foot yam tubers (Amorphophallus paeoniifolius) and also the distribution of starch grains in elephant foot yam tubers (Amorphophallus paeoniifolius). The research method was the purposive sampling method. The object of the research was elephant foot yam tubers (Amorphophallus paeoniifolius). The variables used in this research included the anatomical structure of the elephant foot yam tuber, the shape, type and size of the starch of the elephant foot yam tubers. Data obtained were then analyzed descriptively. Results of this research show that the anatomical structure of elephant foot yam tubers (Amorphophallus paeoniifolius) from the outermost part to the innermost one are the protective tissues, cortex and stele. The growth and development of the anatomical structure of the elephant foot yam tuber is characterized by the presence of periderm which replaces the function of the epidermis, and the increase in the size of the parenchyma cells, as well as the size of the starch grains. Starch form of the elephant foot yam tuber in shapes, namely round and polyhedral. The starch type of elephant foot yam tuber is concentric. The highest mean starch grain size was in E tubers of 17.77 µm. The starch grains in the suweg tubers are of medium size, which is between 10-25 µm. The highest average number of elephant foot yam tuber starch grains was in E tubers with 772 grains. The distribution of starch grains in elephant foot yam tubers is found in the cortex and stele parts, especially in the parenchyma cells. Parenchyma cells containing starch are more commonly found around the vascular bundles.Keywords: elephant foot yam; growth; development; anatomical structure; starch.